METHODOLOGY FOR IMPROVING THE TECHNICAL TRAINING OF YOUNG BOXERS - Nizamova Shaxnoza Ravshonovna (Scholar Express Journals, 2024)
In this article, we will show you a number of necessary instructions and recommendations on the current problems of young boxers at the time of technical training, as well as on the way to finding their solution. This article also covers the analysis of the technical training levels of young boxers.
Keywords: young boxers; technical training; style; results